Hydrogen storage performance of MgH2 under catalysis by highly dispersed nickel-nanoparticle–doped hollow spherical vanadium nitride - Jiaao Wu; Zhihao Liu; Haohua Zhang; Yongjin Zou; Bin Li; Cuili Xiang; Lixian Sun; Fen Xu; Ting Yu (Journal of Magnesium and Alloys)
Magnesium hydride (MgH2) is an exceptional material for hydrogen storage, but its high desorption temperature and slow kinetics limit its applicability. In this study, the hydrogen storage performance of MgH2 was enhanced using highly dispersed Ni-nanoparticle–doped hollow spherical vanadium nitride (Ni/VN), which was synthesized via a solvothermal process. The MgH2 system doped with the synthesized Ni/VN exhibited an outstanding hydrogen-storage capability. Specifically, 5.6 wt.% of H2 was released within 1 h at a relatively low temperature of 513 K, whereas 6.4 wt.% of H2 was released within 180 s at 598 K, followed by an almost complete dehydrogenation after 10 min at 598 K. At 423 K, the developed material absorbed ∼6.0 wt.% of H2 within 5 min. The activation energy for dehydrogenation was determined to be 78.07 ± 2.91 kJ·mol−1, which was considerably lower than that of MgH2 produced by ball milling (120.89 ± 5.74 kJ·mol−1), corresponding to a reduction of 35.4%. It was deduced that the formation of Mg2Ni/Mg2NiH4 (hydrogen pump) through the reaction of Ni nanoparticles during dehydrogenation/hydrogenation facilitated hydrogen transport and synergistically catalyzed hydrogen absorption and desorption by MgH2, improving its hydrogen storage capability. These findings offer novel perspectives for the utilization of MgH2 in large-scale applications.